Pharmacovigilance Studies Involving Healthcare Professionals And Students In Nepal: Impact Assessment On Knowledge, Awareness, Adverse Drug Reactions Reporting And Drug Safety Communications - Palaian, Subish (2010)
The concept of pharmacovigilance is new in Nepal. The present study analyzed the pattern and cost of pharmacotherapy of Adverse Drug Reactions (ADRs) reported to the western regional pharmacovigilance center at Nepal, and evaluated the Knowledge, Attitude and Practices (KAPs) of healthcare professionals in Manipal Teaching Hospital (MTH) towards drug safety. It also aimed at evaluating pharmacovigilance education modules for community pharmacy practitioners, medical, pharmacy and nursing students and analyzed the drug safety communications produced by the western regional pharmacovigilance center.